A Comprehensive Mechanistic Antibacterial and Antibiofilm Study of Potential Bioactive ((BpA)2bp)Cu/Zn Complexes via Bactericidal Mechanisms against Escherichia coli - Sajid Ali; Nazma Faqir; Falak Naz; Muhammad Ishtiaq Jan; Naeem Khan; Amal Alotaibi; Riaz Ullah (Molecules, 2023)
Bacterial resistance to antibiotics and host defense systems is primarily due to bacterial biofilm formation in antibiotic therapy. In the present study, two complexes, bis (biphenyl acetate) bipyridine Cu (II) (1) and bis (biphenyl acetate) bipyridine Zn (II) (2), were tested for their ability to prevent biofilm formation. The minimum inhibitory concentration and minimum bactericidal concentration of complexes 1 and 2 were 46.87 ± 1.822 and 93.75 ± 1.345 and 47.87 ± 1.345 and 94.85 ± 1.466 μg/mL, respectively. The significant activity of both complexes was attributed to the damage caused at the membrane level and was confirmed using an imaging technique. The biofilm inhibitory potential levels of complexes 1 and 2 were 95% and 71%, respectively, while the biofilm eradication potential levels were 95% and 35%, respectively, for both complexes. Both the complexes showed good interactions with the E. coli DNA. Thus, complexes 1 and 2 are good antibiofilm agents that exert their bactericidal actions possibly by disrupting the bacterial membrane and interacting with the bacterial DNA, which can act as a powerful agent to restrain the development of bacterial biofilm on therapeutic implants.